The expression pattern and prognostic relevance of p120-catenin, COL4A2 and SOX10 in glioma - Dumitru, Claudia Alexandra; Schmidt, David Markus Andreas; Neyazi, Belal; Stein, Klaus-Peter; Rashidi, Ali; Kahlert, Ulf Dietrich; Mawrin, Christian; Wilkens, Ludwig; Sandalcioglu, Ibrahim Erol (Frontiers in Oncology, 2026)
Backgroundp120-catenin, COL4A2 and SOX10 are emerging as modulators of glioma pathophysiology and progression. This study aimed to characterize the expression pattern of these markers in glioma tissues with different degrees of malignancy, and tested their prognostic value for the outcome of glioblastoma IDH wild-type (GBM IDHwt) patients, with an additional focus on potential sex-related differences.MethodsAll markers were assessed by immunohistochemistry in tissue microarrays prepared from healthy brain (n=38), astrocytoma grade 2 (n=24), astrocytoma grade 3 (n=22), and GBM IDHwt (n=204) samples. Correlation analyses were performed using Spearman’s Rho, and survival analyses (5-year overall survival and 1-year progression-free survival) were performed using Kaplan-Meier curves, log-rank test and multivariate proportional hazard models.ResultsThe levels of p120-catenin significantly increased with the degree of glioma malignancy (p<0.001; Rho=0.599), while the opposite was observed for COL4A2 (p<0.001, Rho=-0.387) and SOX10 (p<0.001; Rho=-0.293). High levels of p120-catenin significantly associated with and predicted the poor overall survival of GBM IDHwt patients (HR = 1.861, CI = 1.303-2.658, p<0.001) both male (HR = 1.709, CI = 1.077-2.713, p=0.023) and female (HR = 2.141, CI = 1.138-4.028, p=0.018). Conversely, low levels of SOX10 associated with and predicted the poor overall survival of GBM IDHwt patients (HR = 1.552, CI = 1.025-2.352, p=0.038). Interestingly, SOX10 was an independent prognostic factor only in female patients (HR = 2.842, CI = 1.241-6.511, p=0.014). Regarding progression-free survival, p120-catenin was a significant prognostic factor in the whole cohort of GBM IDHwt patients (HR = 2.542; CI = 1.499-4.312; p<0.001) and in the male patients (HR = 2.431; CI = 1.222-4.836; p=0.011), while SOX10 did not predict the progression-free survival in any group of patients. For COL4A2, we found no significant associations with the patients’ outcome, irrespective of sex.Conclusionsp120-catenin is a potential tumor-promoting factor in glioma, and a prognostic marker in GBM. In contrast, COL4A2 and SOX10 appear to act as tumor suppressors in glioma pathophysiology. SOX10 may additionally be a valuable prognostic marker in female GBM patients.